Use of computer technologies in physical education of women of the first mature age - Julia Tomilina (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the improvement of process of physical education of women of the first mature age by means of Pilates with use of information technologies. Material & Methods: the experience of development and deployment of computer technologies in the process of physical education of women of mature age was systematized by means of the analysis of scientific and methodical and special literature and the best pedagogical and coach's practices, which is presented in mass media. The ways of application of computer programs were revealed, and the computer program ''Pilates'' was developed by means of programming in the system Visual Basic. Results: the computer program ''Pilates'', which consists of directory, settlement and recreational blocks, is offered for the purpose of improvement of the process of physical education of women of the first mature age by means of Pilates and increase in their motivation to classes by physical exercises. Conclusions: it is revealed that application of the computer programs has the positive effect in practice of physical education of women of the first mature age. The computer program ''Pilates'' is submitted.